Sheet metal forming : fundamentals - Altan, Taylan; Tekkaya, A. Erman (ASM International, 2012)
Sheet forming fundamentals are thoroughly addressed in this comprehensive reference for the practical and efficient use of sheet forming technologies. The principle variables of sheet forming including the interactions between variables are clearly explained, as a basic foundation for the most effective use of computer aided modeling in process and die design. Topics include stress analysis, formability criteria, tooling, and materials for sheet forming. The book also covers the latest developments in sheet metal forming technology including servo-drive presses and their applications, and advanced cushion systems in mechanical and hydraulic presses.